Landscape evolution in the periglacial zone of Eastern Europe since MIS5: Proxies from paleosols and sediments of the Cheremoshnik key site (Upper Volga, Russia). (16th April 2015) - Rusakov, Alexey; Nikonov, Andrei; Savelieva, Larisa; Simakova, Alexandra; Sedov, Sergey; Maksimov, Fedor; Kuznetsov, Vladislav; Savenko, Viktor; Starikova, Anna; Korkka, Maria; Titova, Darya
Abstract: A variety of studies of the re-examined (new exposure) Late Pleistocene key section Cheremoshnik (East European plain, middle of the Volga Basin of Yaroslavl) was conducted on a new methodological level using modern methods. For the first time, a series of paleosols (MIS5–MIS1) from the section offering significant information in regard to chronostratigraphy and landscape evolution have been studied in detail and dated. An excavation ∼7 m deep reveals a soil-sediment stratum which formed over the course of ∼115 ka in an accumulative beam-like terrace and consists of five lithological layers and six pedostratigraphical units. The base of the section was determined to be an Early Mikulino peat-dark humus paleosol which marked incipient subaerial pedogenesis on the Moscow (Riss II) moraine and was covered with a thickness of gyttja with a peat horizon (Histosol) which had formed 114–115 ka and was reliably dated using uranium–thorium dating. The following paleosols were successfully identified within the series of weak stone gullied-channel sediments within the Valdai (Wűrm) thickness (from bottom to top): (1) Bryansk paleosol (MIS3) – Gleysol – with three pedogenesis rhythms; (2) Trubchevskaya paleоsol – Gleyic Turbic Cryosol (MIS2) and (3) pedosediment formed at the end of the Bӧlling interstadial (MIS2). Terminal Pleistocene formations are marked with a gravelly stratum on the section's surface formed during the Preboreal period. Recent Regosol formed on loess-like loam deposits was identified at the top of the whole soil-sediment stratum. The 14 C age of the paleosol humus varied between 27, 500 and 11, 400 cal. BP. The paleosols represent the northernmost occurrence of MIS5–MIS2 fossil soil in Europe, dominated by features of gleyzation, cryogenic aggregation, cracking, and humus and peat formation. Pollen analysis results allowed estimation of changes in vegetation cover, climatic conditions and the age of deposit sedimentation for the period from the Moskow Late Glacial to the Valdai Late Glacial and early Holocene times. Successive stages in the development of vegetation, high contents of alder and hazel pollen and the climax and distinct appearance of broadleaf trees relate the formation of biogenic sediments (LPAZ 2–6) in the Cheremoshnik section to the Mikulino Interglacial. Valdai (MIS4–MIS2) glacial sediment is absent within the investigated area.